African Red Slip Ware in Tarquinia and in the ager Tarquiniensis in Late Antiquity - Arioli, Luca (Rei Cretariae Romanae Fautorum Acta, 2024)
Tarquinia was among the largest cities of South Etruria. Excavations by the University of Verona in the so-called domus “of the Mithraeum” and in the forum are providing the first data on the city in Roman and Late antique times, as well as on its pottery. This paper aims at analysing the consumption of African Red Slip Ware in the city and its territory by providing a preliminary presentation of the finds from the domus. These data are compared with a survey of published ARS finds from the sites of the ager Tarquiniensis to evaluate their potential for the reconstruction of local consumption and distribution patterns during Late Antiquity and their significance for the evaluation of the continuity of settlement in the area. ARS supply continues during the 5th century and the central decades of the 6th but decreases after the Gothic War and ceases after the Lombard conquest.